The effects of conflict pollution on environmental sustainability: A modern adaptation of the just war theory to foreign policy as a method of pollution prevention - Spiva Daisy (E3S Web of Conferences)
As it stands, the environment is confronted by an unprecedented extent of human activity from ongoing technological innovation, population growth, and resource consumption. This current state of development isn’t sustainable without interventive measures to mitigate risks of ecosystem destabilization and eventual collapse. Though human impact on the environment isn’t necessarily negative, these perturbations in ecological conditions are of substantial concern due to an accelerated rate of modification and degradation that compromise geological processes. Historically, Earth and its environment underwent several periods of change, such as glacial-interglacial cycles from astronomical forces; however, these fluctuations are natural constituents of planetary development and the phase of slow surface evolution. In contrast, the inception of conflict is an additional and artificial disturbance with the propensity to cause catastrophic effects, despite strategies to counteract the harmful byproducts of societal operations. In terms of air, water, and soil resources, outbreaks of conflict are a potential source of rampant pollution and their environmental costs are referenced within international law with limited protection. Regardless of outlined provisions that prohibit the direct destruction of the environment as a weapon of war, contemporary advancements in military organization and their technological capabilities put the environment at greater risk than ever before in human history. Periods of active combat also undermine environmental mitigation initiatives by allocating the necessary funding, research, and workforce elsewhere due to the inherently demanding nature of conflict. Thus, I argue a modern adaptation to the Just War Theory and its application in foreign policy can further inform efforts of environmental protection and pollution prevention, ensuring global sustainability as well as forestalling the onset of irreversible damage.